A New method to optimize BGP routes using SDN and reducing latency - Elguea, Lorenzo M.; Martínez Ríos, Félix Orlando (My University, 2018)
Latency on Internet mainly depends on the distance that packets travel in WAN networks1. This latency can be reduced if the hops between autonomous systems are reduced. This is the main function of the BGP protocol that is used by default in all the ISPs, but the lack of announcement of some network segments causes some routes to increase. This paper proposes a simple method to detect the routes that can be optimized and also a method using SDN to correct them. The first step is to determine which routes can be optimized, that is, those that are sent to a neighbor when they travel the greater distance, although this can not be determined by the router since it does not analyze all the routes that BGP receives in context. The second step is to add the new routes to the router, also by BGP, so that the router uses them. © 2018 The Authors. Published by Elsevier Ltd.
Keywords: BGP; Latency; Network Optimization; SDN; Artificial intelligence; Routing protocols; Autonomous systems; Network optimization; Network segment; Simple method